2012
DOI: 10.1111/j.1365-2966.2012.21896.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the integrated Sachs-Wolfe effect revisited

Abstract: We revisit the state of the integrated Sachs-Wolfe (ISW) effect measurements in light of newly available data and address criticisms about the measurements which have recently been raised. We update the data set previously assembled by Giannantonio et al. to include new data releases for both the cosmic microwave background (CMB) and the large-scale structure (LSS) of the Universe. We find that our updated results are consistent with previous measurements. By fitting a single template amplitude, we now obtain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
133
7

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 116 publications
(200 reference statements)
11
133
7
Order By: Relevance
“…As was mentioned already, a strong point of our results is the excellent compatibility between the ISW amplitude estimates with respect to the expected value. While our estimation deviates by about 0.5σ from the expected value, the Giannantonio et al (2012) result exceeds it by about 1σ and Ho et al (2008) is higher by 2σ.…”
Section: Ccf Smhwcovcontrasting
confidence: 81%
See 4 more Smart Citations
“…As was mentioned already, a strong point of our results is the excellent compatibility between the ISW amplitude estimates with respect to the expected value. While our estimation deviates by about 0.5σ from the expected value, the Giannantonio et al (2012) result exceeds it by about 1σ and Ho et al (2008) is higher by 2σ.…”
Section: Ccf Smhwcovcontrasting
confidence: 81%
“…For instance, Ho et al (2008) and Giannantonio et al (2012) found 3.7σ and 4.4σ detections, respectively. Compatibility with the former is below 1σ, while there is more tension (about 1.5σ) with the latter.…”
Section: Ccf Smhwcovmentioning
confidence: 97%
See 3 more Smart Citations